2017
DOI: 10.1002/2016wr019722
|View full text |Cite
|
Sign up to set email alerts
|

Controls on solute concentration‐discharge relationships revealed by simultaneous hydrochemistry observations of hillslope runoff and stream flow: The importance of critical zone structure

Abstract: We investigated controls on concentration‐discharge relationships of a catchment underlain by argillite by monitoring both groundwater along a hillslope transect and stream chemistry. Samples were collected at 1–3 day intervals over 4 years (2009–2013) in Elder Creek in the Eel River Critical Zone Observatory in California. Runoff at our study hillslope is driven by vadose zone flux through deeply weathered argillite (5–25 m thick) to a perched, seasonally dynamic groundwater that then drains to Elder Creek. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 54 publications
7
58
3
Order By: Relevance
“…By coupling our understanding of the subsurface hydrology of our sites (Dralle et. al, 2016; Druhan et al, ; Hahm et al, ; Kim et al, ; Link et al, ; Oshun et al, ; Rempe & Dietrich, ; Rempe et al, ; Salve et al, ) with wetted channel observations at the beginning and end of the summer dry season, our study demonstrates the connection between critical zone structure and the extent and duration of wetted channels.…”
Section: Introductionsupporting
confidence: 64%
“…By coupling our understanding of the subsurface hydrology of our sites (Dralle et. al, 2016; Druhan et al, ; Hahm et al, ; Kim et al, ; Link et al, ; Oshun et al, ; Rempe & Dietrich, ; Rempe et al, ; Salve et al, ) with wetted channel observations at the beginning and end of the summer dry season, our study demonstrates the connection between critical zone structure and the extent and duration of wetted channels.…”
Section: Introductionsupporting
confidence: 64%
“…Although other researchers have found that many of the analytes they measured displayed chemostatic behaviour and had flat C‐Q shapes with slopes below | b | < 0.2 (Basu et al, ; Godsey et al, ; Hunsaker & Johnson, ; Kim, Dietrich, Thurnhoffer, Bishop, & Fung, ; Thompson et al, ), we found that all positive and negative Honeysuckle Creek C‐Q relationships, with the exception of Mg 2+ at the upper flume, were strongly significant with slopes greater than | b | > 0.2. Our results did generally agree with the findings of these researchers that solute concentrations vary less than discharge.…”
Section: Discussioncontrasting
confidence: 73%
“…Given the distinctive roles of direct and indirect storages in the process of discharge generation, their physical arrangement and respective energetic statuses may have implications for hydraulic transport and hydrological model formulation. For example, at Elder Creek, Kim, Dietrich, Thurnhoffer, Bishop, and Fung () show that chemostasis in the stream can be partially explained by large volumes of tension‐held unsaturated moisture in soil and weathered rock, which is physically positioned above hillslope groundwater tables, buffering incoming rains and draining chemically reacted waters to the saturated zone during recharge events. In contrast, Dry Creek exhibits greater dilution of major cations at high flows, consistent with shorter residence times and lower fluid–solid interactions during high run‐off events dominated by shallow subsurface and saturation overland flow (Hahm, Druhan, Rempe, & Dietrich, ).…”
Section: Discussionmentioning
confidence: 99%